Environmentally driven transcriptomic and metabolic changes leading to color differences in “Golden Reinders” apples - Fernández-Cancelo, Pablo; Iglesias-Sanchez, Ariadna; Torres-Montilla, Salvador; Ribas-Agustí, Albert; Teixidó, Neus; Rodriguez-Concepcion, Manuel; Giné-Bordonaba, Jordi (Frontiers in Plant Science, 2022)
Apple is characterized by its high adaptation to diverse growing environments. However, little is still known about how different environments can regulate at the metabolic or molecular level specific apple quality traits such as the yellow fruit peel color. In this study, changes in carotenoids and chlorophylls, antioxidants as well as differences in the transcriptome were investigated by comparing the peel of ‘Golden Reinders’ apples grown at different valley and mountain orchards. Mountain environment favored the development of yellow color, which was not caused by an enhanced accumulation of carotenoids but rather by a decrease in the chlorophyll content. The yellow phenotype was also associated to higher expression of genes related to chloroplast functions and oxidative stress whereas plastid morphology analysis revealed the presence of membranous structures tentatively derived from thylakoids and likely associated to enhanced ROS levels. Time-course analysis over the last stages of apple development and ripening, in fruit from both locations, further revealed that the environment differentially modulated isoprenoids and phenylpropanoids metabolism and pointed out a key role for H2O2 in triggering apple peel degreening. Overall, the results presented herein provide new insights on how different environmental conditions regulate pigment and antioxidant metabolism in apple leading to noticeable differences in the apple peel color.